The methods of inversion and the maximum likelihood estimation in acoustic tests of industrial sources in the environment - Stryczniewicz, L. (Archives of Acoustics, 2006)
Determining an acoustic model of a factory is a topic connected to the noise sources identification in the factory, their localization and acoustic parameters. In order to determine the source parameters correctly, it is necessary to use the whole available knowledge accessed in acoustic measurements and the knowledge obtained a priori (e.g. on the basis of producers’ catalogues of equipment). To solve this problem the method of the acoustic inversion was used with the maximum likelihood estimation. The biggest advantage of this method is the possibility to use the information concerning accuracy of the determined a priori sound power of noise sources and indicating the importance of the sound pressure level values in measurement areas. The theoretical assumptions of the method, its adjustment to the industrial conditions as well as tosome computer simulations are presented in the paper.